Clinical, immunologic and genetic characterization of Colombian patients with cutaneous recalcitrant warts - Rojas, Julián; Jouanguy, Emmanuelle; López, Juan Álvaro; Franco, José Luis; Arias, Andrés Augusto (Iatreia, 2021)
Inborn errors of innate and intrinsic immunity are monogenic diseases that result in predisposition to a whole spectrum of infectious diseases (for example, viruses)(1). Cutaneous warts caused by Human Papillomavirus (HPV) infection has an incidence that range from 10% in the general population(2). These lesions are relatively common and most warts regress spontaneously. However, in some individuals, these warts persist for > 2 years without response to conventional therapy (cryotherapy, salicylic acid or bleomycin), and they are called recalcitrant warts (RW)(2-4). Host defense against HPV relies on intact and functioning cellular immunity including T cell, natural killer cell cytotoxicity and intrinsic immunity. Therefore, in patients in whom warts are recalcitrant, concern for immune defects is raised (5). RW have been documented in patients with a few inborn errors of immunity, either in combination with broad infectious phenotypes (combined immunodeficiencies), and HIV+ and transplanted patients(6, 7). On the another hand, is well documented that patients with Epidermodysplasia Verruciformis present a specific genetic predisposition to beta-HPV infection, but only very few is known about genetic susceptibility to recalcitrant warts and to our knowledge there is not studies searching for monogenic defects associated with RW(7-9). Therefore, we hypothesized that susceptibility to RW due to HPV viruses in otherwise healthy individuals, might be due to underlying genetic defects in intrinsic and innate immunity.